Incentivizing BECCS—A Swedish Case Study - Zetterberg, Lars; Johnsson, Filip; Möllersten, Kenneth (Frontiers in Climate, 2021)
Negative CO2-emissions are prevalent in most global emissions pathways that meet the Paris temperature targets and are a critical component for reaching net-zero emissions in Year 2050. However, economic incentives supporting commercialization and deployment of BECCS are missing. This Policy and Practice Review discusses five different models for creating incentives and financing for BECCS, using Sweden as an example: 1) governmental guarantees for purchasing BECCS outcomes; 2) quota obligation imposition on selected sectors to acquire BECCS outcomes; 3) allowing BECCS credits to compensate for hard-to-abate emissions within the EU ETS; 4) private entities for voluntary compensation; and 5) other states acting as buyers of BECCS outcomes to meet their mitigation targets under the Paris Agreement. We conclude that successful implementation of BECCS is likely to require a combination of several of the Policy Models, implemented in a sequential manner. The governmental guarantee model (Model 1) is likely to be required in the shorter term, so as to establish BECCS. Policy Models 2 and 3 may become more influential over time once BECCS has been established and accepted. Model 3 links BECCS to a large carbon-pricing regime with opportunities for cost-effectiveness and expanded financing. We conclude that Policy Models 4 and 5 are associated with high levels of uncertainty regarding the timing and volume of negative emissions that can be expected- Thus, they are unlikely to trigger BECCS implementation in the short term, although may have roles in the longer term. Based on this study, we recommend that policymakers carefully consider a policy sequencing approach that is predictable and sustainable over time, for which further analyses are required. It is not obvious how such sequencing can be arranged, as the capacities to implement the different Policy Models are vested in different organizations (national governments, EU, private firms). Furthermore, it will be important to ensure that BECCS and the associated biomass resource are not overexploited. A well-designed policy package should guarantee that BECCS is neither used to postpone the reduction of fossil fuel-based emissions nor overused in the short term as a niche business for “greenwashing” while not addressing fossil fuel emissions.